Pengetahuan, Sikap Dan Dukungan Tenaga Kesehatan Tentang Penggunaan Alat Kontrasepsi Pada Wanita Usia Subur - Mufidah, Dewi Khasanatul; Armini, Ni Wayan; Budiani, Ni Nyoman (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Â The participation of women of childbearing age who have not used contraception in the UPTD Puskesmas 1 East Denpasar area is still high at 5,900 people (39.68%). The aim of this research is to describe the knowledge, attitudes and support of health workers for women of childbearing age who do not yet use contraception. This research uses a descriptive research method with a purposive sampling technique. This research was carried out in the UPTD area of East Denpasar Community Health Center 1 in collaboration with enumerators. The population in this study was 5,900 women of childbearing age, with a sample size of 108 women of childbearing age. This study uses inclusion and exclusion criteria. The research results of respondents' knowledge were classified as good (57.4), respondents' attitudes were classified as positive (83.3%), support from health workers from all categories was classified as supportive (89.27%). The conclusion is that knowledge is good, but there are still some women of childbearing age who have sufficient and insufficient knowledge. The attitudes of women of childbearing age are positive and negative, influenced by myths, cultural beliefs, concerns about side effects, and the bad experiences of other people. Support from health workers has been supportive, but education and effective communication for women of childbearing age needs to be increased. It is recommended that the Puskesmas carry out regular evaluations of outreach activities, so that all WUS can receive more optimal services